Relacje pomiędzy metropolitą Andrzejem Szeptyckim a ukraińską inteligencją - Kubasik, Adam (Saeculum Christianum. Pismo Historyczne, 2019)
The Metropolitan Archbishop Andrey Sheptytsky was the head of the Greek Catholic Church in Eastern Małopolska in 1901-1946. When he assumed the duties of a bishop, he realised that work with the intelligentsia would be more difficult than with other people. However, he still wished to be their spiritual leader in their Christian life. He never wanted to set the clergy against the intelligentsia; he did not believe they were in opposite camps. He summoned those who declared they affiliation with the Greek Catholic Church to manifest it in their everyday living. Moreover, he opposed those who demanded that the Greek Catholics join the Orthodox Church for the sake of national unity of the Ukrainians. Many people representing the world of culture and science considered him as the most important defender of the Ukrainian nation’s rights.